Parallel roles of transcription factors dFOXO and FER2 in the development and maintenance of dopaminergic neurons. - Damla Tas (PLoS Genetics, 2018)
Forkhead box (FOXO) proteins are evolutionarily conserved, stress-responsive transcription factors (TFs) that can promote or counteract cell death. Mutations in FOXO genes are implicated in numerous pathologies, including age-dependent neurodegenerative disorders, such as Parkinson's disease (PD). However, the complex regulation and downstream mechanisms of FOXOs present a challenge in understanding their roles in the pathogenesis of PD. Here, we investigate the involvement of FOXO in the death of dopaminergic (DA) neurons, the key pathological feature of PD, in Drosophila. We show that dFOXO null mutants exhibit a selective loss of DA neurons in the subgroup crucial for locomotion, the protocerebral anterior medial (PAM) cluster, during development as well as in adulthood. PAM neuron-targeted adult-restricted knockdown demonstrates that dFOXO in adult PAM neurons tissue-autonomously promotes neuronal survival during aging. We further show that dFOXO and the bHLH-TF 48-related-2 (FER2) act in parallel to protect PAM neurons from different forms of cellular stress. Remarkably, however, dFOXO and FER2 share common downstream processes leading to the regulation of autophagy and mitochondrial morphology. Thus, overexpression of one can rescue the loss of function of the other. These results indicate a role of dFOXO in neuroprotection and highlight the notion that multiple genetic and environmental factors interact to increase the risk of DA neuron degeneration and the development of PD.